Film and the city : the urban imaginary in Canadian cinema (2014)
This book is a study of the focus on Canada’s urban environments that has emerged in Canadian narrative cinema over the past decades. It draws its inspiration in part from another recent trend, that toward interdisciplinary approaches. In what follows, I seek to integrate insights from three well-established fields—Canadian studies, with its ongoing exploration of national-identity formation for both individuals and collectives; film studies, which contributes concepts of genre, authorship, and audience; and urban studies perspectives on the built environment and the urban experience. Mark Shiel, co-editor of Cinema and the City, argues that interdisciplinary approaches “can be profoundly useful and fruitful in addressing key issues.”1 Ideally, interdisciplinarity creates intellectual linkages that generate fresh approaches to subject matter. Shiel’s work, for example, uses interdisciplinary methods to generate what he calls “a sociology of cinema.”2 My goal is different: I want to link the construction of urban identity in a film text with the urban influences on the filmmaker and the film’s audience. Through the integration of theoretical, methodological, and empirical approaches from three different fields, I seek to move the discussion of film and the city beyond the conventional boundaries of any particular field of scholarship. By linking films and cities and analyzing how the two are related, I also hope to offer a distinctive statement about contemporary Canadian identity—to clarify how Canadian urban cinema contributes both to our understanding of urban realities and to our efforts to articulate what it means to be Canadian.